The Studies of Architectural Design Method - Djoko Indrosaptono; Tri Susetyo Andadari; Alfanadi Agung Setiyawan (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2021)
The design processes and strategies applied to each architect in carrying out their design tasks are different. The stages in producing architectural work can be based on the theory of certain design methods, intuition or design experience from each architect. As an architect, it is mandatory to know the design process in accordance with existing methods. There are several variables in the design method according to Jones and Schmitt. And this study aims to find the variables most widely used by 8 architects in designing. Including the average of the variables it uses. The method used in this research is quantitative method with one way ANOVA (analysis of variant) as its statistical analysis, by examining the mean difference between the research objects. The literature study was used to obtain an analysis of the design process and the methods used by 4 well-known architects as their secondary empirical data source, while field observations in the form of direct interviews were carried out to obtain the reality of the design process for 4 local architects with various backgrounds and characteristics as well as different architectural works. The end result shows that the average level of architects in the use of research variables is not much different and the design process variables that are most often used by architects in carrying out architectural designs, are the clarity of the need for the design function, the use of the drawing system and the design results that are meaningful and logical.